Esther Shephard. - Unknown:::Creator::::::::::::
Written on verso: "Esther Shephard." Esther Shephard's most important academic appointment was in the English Department at San Jose State College, where she taught ca. 1939-1959. During this period her poetic retelling of an ancient Chinese legend, "The Cowherd and the Sky Maiden," was published in 1950. It was produced as an opera in 1952, with music by John Verral and staged by John Ashby Conway, at the University of Washington. http://www.lib.washington.edu/SpecialColl/findaids/docs/papersrecords/ShephardEsther0994.xml